2022
DOI: 10.1089/heq.2021.0120
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Disparities and Mental Health Impacts Among Cancer Survivors During the COVID-19 Pandemic

Abstract: Introduction: Food insecurity can negatively impact adherence and receipt of high-quality cancer care. The purpose of the study was to (1) compare the prevalence of COVID-19-associated food insecurity by cancer history and (2) examine determinants associated with COVID-19-related food insecurity among cancer survivors. Methods: We used nationally representative data from the 2020 COVID-19 Household Impact Survey ( n =10,760). Our primary expos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For example, it was found that the determinants of food insecurity among individuals with cardiometabolic conditions, during the pandemic, included Hispanic race/ethnicity, an educational degree lower than a baccalaureate, a household of less than $100,000, and having Medicaid or no insurance (Camacho-Rivera et al, 2022a). Similar factors associated with an increased risk of food insecurity were seen among cancer survivors, including lower levels of education, household income of less than $30,000 per year, and having Medicaid or no insurance coverage (Camacho-Rivera et al, 2022b).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, it was found that the determinants of food insecurity among individuals with cardiometabolic conditions, during the pandemic, included Hispanic race/ethnicity, an educational degree lower than a baccalaureate, a household of less than $100,000, and having Medicaid or no insurance (Camacho-Rivera et al, 2022a). Similar factors associated with an increased risk of food insecurity were seen among cancer survivors, including lower levels of education, household income of less than $30,000 per year, and having Medicaid or no insurance coverage (Camacho-Rivera et al, 2022b).…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that racial/ethnic minority adult populations experiencing pulmonary chronic conditions (e.g., asthma) reported elevated mental health complications during the pandemic (Wei et al, 2021). However, less attention has been supplied to the interplay between asthma, mental health symptoms, and broader social inequities in food insecurity experienced by U.S. Latinx adults (Camacho-Rivera et al, 2022a, 2022b).…”
Section: Introductionmentioning
confidence: 99%